Rancang Bangun Sistem Informasi Akademik Pada Innovative Learning Center - Wibisono, Dani Gunawan; Widodo, Arifin Puji; Susanto, Teguh (Jurnal JSIKA, 2014)
Innovative Learning Center (ILC) is an English course that was founded in 2007 with a vision to improve the English language skills in aspects of Â learning such as listening, speaking, writing, reading and grammar as well as being the leading English language tutoring in Sidoarjo. In ILC, system that handle administrative processes is already exist using Excel but considered inadequate. There is a lack of useful reports for management for the purpose of measuring the performance of ILC within certain period. In addition to said problem, there are also other problem where the tutors are having insufficient information about the performance of their class. During the teaching session, the tutors teach without knowing each studentâs progress. The result is that students who have poor grades canât be known early. Other problems also arise from the students and parents caused by lack of communication between the ILC with parents. As a result, parents are often misinformed about the development of their academic activities. Therefore, to resolve these problems, there is a need to build an Academic Information System that manage information of students, academic information and Â financial information. The Academic Information System must be capable of producing useful reports about ILCs performance and financial information for the owner. The System must also capable of providing class academic information for tutors and student academic information to parents or students. Academic Information Systems can provide the information needed by the owner, tutors and students.